A Review of International Entrepreneurship as Part of Broader Opportunity Research : Topic Modelling Approach - Puhakka, Vesa; Ojala, Arto (Springer, 2021)
Although international entrepreneurship reviews have made a significant contribution to the subject’s knowledge, researchers have not unleashed its full potential. This review provides an understanding of the deeper development processes and structures in international entrepreneurship, focusing on international entrepreneurship’s role in broader opportunity research. We begin by elaborating on a topic modelling approach to look at latent structures of scientific discussion. We then review the contents, influence, and impact of international entrepreneurship in opportunity research. Finally, we present issues that future research could take into account both theoretically and methodologically.
Keywords: fi=Kansainvälinen liiketoiminta|en=International Business|